Snapshot of an acute palliative care unit in a tertiary cancer hospital. Issue 4 (16th October 2013) - Reddy, Akhila; Vidal, Marieberta; de la Cruz, Maxine; Yennurajalingam, Sriram; Bruera, Eduardo
Abstract Most palliative care (PC) programs in the United States provide consultation services that assist the primary medical team with issues ranging from controlling patients' symptoms to initiating end-of-life discussions. This approach may be sufficient to address many patients' needs. However, for certain patients with complex medical and psychosocial issues, a better alternative is a more streamlined approach that can be provided in an acute palliative care unit (APCU), where the PC staff assumes the role of the primary team. An APCU is a specialized unit that delivers highly sophisticated care with professionals from various disciplines working together to improve the quality of life of patients and their families. However, descriptions of the process of delivering PC in the APCU are limited. In this special report, we portray a single day with a series of patients whose care was managed at our APCU to illustrate the unique components of an APCU that allow holistic care for patients with multiple complex medical and psychosocial issues.